(untitled) (International journal of medical sciences, 2026)
Esthetic dental implantology has become a critical component of modern restorative dentistry, emphasizing both functional efficiency and visual harmony. The Implant-Guided Concept (IGC) represents a contemporary approach that integrates digital diagnostics, 3D planning, and surgical guidance to optimize implant positioning and esthetic outcomes. This study explores the principles, clinical applications, and advantages of IGC in esthetic zones, highlighting its role in soft tissue preservation, bone management, and prosthetic planning. Evidence from recent literature indicates that guided implant placement enhances predictability, improves patient satisfaction, and minimizes intraoperative errors. While challenges such as high cost, technical complexity, and anatomical limitations exist, ongoing research and technological advances continue to improve the accessibility and reliability of IGC protocols. Overall, the IGC approach is a patient-centered, evidence-based strategy that significantly enhances esthetic and functional outcomes in dental implantology.